Preconception health risks among women of reproductive age in Sub-Saharan Africa: a systematic review of implications for preconception care - Gebremedhin Gebreegziabher Gebretsadik; Andargachew Kassa Biratu; Amanuel Gessessew; Zohra S. Lassi; Alemayehu Bayray Kahsay; Afework Mulugeta (Journal of Health, Population and Nutrition)
Abstract Introduction Although preconception health risks are strongly linked to adverse pregnancy outcomes and offer opportunities to improve women’s health, consolidated evidence remains limited in Sub-Saharan Africa (SSA). This review aims to synthesize evidence on preconception health risks in SSA, a region with the highest global rates of maternal and neonatal mortality and morbidity. Methods We searched PubMed/MEDLINE, African Index Medicus, ScienceDirect, and Google Scholar for studies published up to June 30, 2023. Two reviewers independently assessed study quality using Joanna Briggs Institute tools. Studies with at least one modifiable preconception risk were included. Due to inconsistencies in outcome measurements, participant variability, and high heterogeneity, a meta-analysis was not reported. Findings were summarized in text, figures, and tables. Results In the review, researchers selected 83 articles from a total of 3,425 retrieved articles. Overall, this review revealed a high proportion of preconception health risks among the participants which includes underweight (0.64% to 36.2%), overweight (8.3% to 76.7%), anemia (36.7% to 58.1%), unintended pregnancy (4.2% to 94.3%), alcohol intake (5.3% to 68.7%), smoking (1.1% to 20.3%), chewing khat (9.9% to 27.6%), history of chronic medical conditions (2% to 16.6%), a history of adverse pregnancy outcomes (11% to 51.9%), sexually transmitted infections (1.3% to 29.2%), psychosocial distress (13.9% to 60%), and intimate partner violence (6.7% to 43.7%). Conclusion The systematic review found that numerous women in  SSA encounter various preconception health risks factors. Therefore, the governments of respective countries need to give emphasis and adopt policies to integrate preconception care services in to the existing healthcare system so that both financial and human resources need to be mobilized. There is gaps in research, as the true burden of preconception health risks may be underestimated due to fragmented risk assessment methods. Review registration: (PROSPERO: CRD42023446801)